Comparative analysis of different diagnostic methods for detecting root canal orifices by a student and an experienced endodontist – initial report - Banaszek, Katarzyna; Domagała, Ewa; Nawarycz, Tadeusz; Sokołowski, Jerzy (Journal of Stomatology, 2016)
Introduction. Making an error at the initial stage of treatment excludes its successful outcome. Complex anatomy and morphology of canals especially in multi-canal teeth make these teeth particularly vulnerable to complications and treatment failure. Aim of the study. To assess the success rate of four methods of canal orifice diagnostics and the efficacy of the clinical operator’s experience (S–student, E– endodontist). Methods. Fifty extracted human molars were divided into five groups and diagnosed using a basic method – an endodontic probe (BM), M1 – with a Kerr file, M2 – with a Kerr file after staining with methylene blue, M3 – with a Kerr file and a dental operating microscope, and M4 – with a Kerr file and an operating microscope after staining with methylene blue. Each tooth was evaluated twice by S and E. The Student t-test, contingency tables and Cohen’s kappa coefficient of agreement were used. Results. Mean values of canal orifices properly diagnosed by S and E with M3 and M4 were the same and higher than BM. M1 and M2 had lower values of Cohen’s kappa coefficient and should be interpreted as the methods of lower diagnostic agreement but higher sensitivity to the operators’ skills. Conclusions. The use of a dental microscope offers better diagnostic efficiency and lower sensitivity to the operators’ skills, and thus should be recommended both in students’ training and in dental practice.